2018
DOI: 10.1155/2018/2472137
|View full text |Cite
|
Sign up to set email alerts
|

Side Population: Its Use in the Study of Cellular Heterogeneity and as a Potential Enrichment Tool for Rare Cell Populations

Abstract: There is still much to learn about the cells used for cell- and gene-based therapies in the clinical setting. Stem cells are found in virtually all tissues in the human body. As a result, cells isolated from these tissues are a heterogeneous population consisting of various subpopulations including stem cells. Several strategies have been used to isolate and define the subpopulations that constitute these heterogeneous populations, one of which is the side population (SP) assay. SP cells are identified by thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…In addition, a quiescent VESC population was identified by using flow cytometry to carry out the side population (SP) assay [ 48 ], which consists of measuring the efflux rate of a fluorescent dye, such as Hoechst 33342. Stem cells may indeed efflux Hoechst 33,342 at a faster rate as compared to differentiated cells [ 49 ] due to the higher expression of a novel stem cell marker, the ABC-binding cassette transporter ABCG2. These endothelial–SP cells were dispersed along the vascular tree, showed robust proliferative potential, and were able to promote neovascularization and rescue blood perfusion in mouse models of hindlimb ischemia [ 47 ].…”
Section: Endothelial Colony-forming Cells: Origin Mechanisms Of Amentioning
confidence: 99%
“…In addition, a quiescent VESC population was identified by using flow cytometry to carry out the side population (SP) assay [ 48 ], which consists of measuring the efflux rate of a fluorescent dye, such as Hoechst 33342. Stem cells may indeed efflux Hoechst 33,342 at a faster rate as compared to differentiated cells [ 49 ] due to the higher expression of a novel stem cell marker, the ABC-binding cassette transporter ABCG2. These endothelial–SP cells were dispersed along the vascular tree, showed robust proliferative potential, and were able to promote neovascularization and rescue blood perfusion in mouse models of hindlimb ischemia [ 47 ].…”
Section: Endothelial Colony-forming Cells: Origin Mechanisms Of Amentioning
confidence: 99%
“…Verapamil is used to validate that the decrease of fluorescence in SP cells is due to efflux only. It blocks the efflux pumps, and in turn, there is a decrease in the SP cells as the dye is retained ( Wolmarans et al, 2018 ). We observed that as the BC cells acquired radioresistance, there is an increase in the SP cells ( Supplementary Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the IC 50 values of cisplatin and doxorubicin in SP cells were higher compared with nSP cells, whereas SP cells were more sensitive to 4,4'-SAD compared with nSP cells. SP cells, which are involved in multidrug resistance and tumor initiation, express high levels of aBc transporters, including aBcG2, to expulse Hoechst 33342 dye (4,21). Moreover, previous studies have revealed that Sad reduces the expression of aBcG2 and percentage of SP cells in lung cancer cells (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…although at the beginning treatments can partially or completely shrink tumors, relapse and metastasis lead to treatment failure due to the existence of cancer stem cells (cScs) (2,3). Moreover, cells isolated by fluorescence-activated cell sorting techniques based on Hoechst 33342 efflux are known as side population (SP) cells and harbor cScs properties, such as self-renewal and multipotential differentiation (4). The most significant feature of SP cells is their ability to discharge Hoechst 33342 from cells due to the high expression of aTP binding cassette (aBc) transporter proteins (5).…”
Section: Introductionmentioning
confidence: 99%